Elastic constants and optical phonon frequencies of BX (X= P, As, and Sb) semiconductors: Semi-empirical prediction - Daoud, Salah; Kumar Saini, Pawan; Rekab-Djabri, Hamza (International Journal of Physical Research, 2020)
Based on some simple empirical formulas established by Adachi in, Properties of group-IV, III-V and II-VI semiconductors, John Wiley & Sons, Chichester (2005), and the experimental lattice constants reported in the literature; the present work aims to predict the elastic constants and some other significant properties of cubic zinc-blende boron compounds (BP, BAs and BSb). The obtained values of C12and C44 are in general good agreement with other data of the literature, while C11 and B are slightly lower. The zone-center longitudinal optical (LO) and transverse optical (TO) phonon frequencies are also obtained. The LO and TO phonon frequencies of BP compound were found at 866.6and 834.5 cm–1, respectively; these of BAs were found at 731.3 and 727.1 cm–1, respectively; while for the BSb narrow-gap semiconducting compound were found at around 598.3and 586.2 cm–1, respectively. These two later values are in general slightly lower than the calculated values, and the observed Raman spectroscopy values reported in the literature.